Book Review: Free Cyntoia: My search for redemption in the American prison system: - Smoyer, Amy B. (Affilia, 2021)
Keywords: book.review; dept.swk; peer-reviewed

The everything else - Smoyer, Amy B. (Sensory Penalities, 2021)
Sensory Penalties aims to reinvigorate a conversation about the role of sensory experience in empirical investigation. It explores the visceral, personal reflections buried within forgotten criminological field notes, to ask what privileging these sensorial experiences does for how we understand and research spaces of punishment and social control.
Keywords: dept.swk

Masculine embodiment among sexual minorities in a women’s prison - Smoyer, Amy B.; Divita, David; Perrault, Allison (Australian Social Work, 2021)
Sexual minority women are disproportionately incarcerated and more likely to experience structural and interpersonal violence while incarcerated than heterosexual cisgender women. To build knowledge about this population and inform social work practice, theories of embodiment were used to conduct thematic analysis of five interviews with lesbian, gay, bisexual, transgender, and queer masculine-identified people who had been incarcerated in a women’s prison. This analysis explicates how participants used bodily practices to construct gender and communicate identity to themselves and others. Uniforms, prison regulations, and physical manifestations of female embodiment complicated these efforts. Participants described the ways in which they monitored and evaluated their own bodies while also managing the constant surveillance of their bodies by others. Taken together, these findings explicate the ways in which participants’ bodies were produced both through their actions and the external gaze of others. Implications for social work include exploration of language and masculinity in practice settings and suggestions for correctional policies. Findings encourage inclusion of non-binary frameworks and increased attention to the embodied self in order to expand understandings of human behaviour in the social environment. IMPLICATIONS Interpret with caution any information about gender identity surmised from intake forms and observation of clients’ bodily practices. Ask clients to describe their gender identity. Prioritise correctional policies that promote the health and safety of incarcerated people and staff over policies that enforce social norms related to gender and have no implications on security. Encourage re-entry service providers to collaborate with LGBTIQA+ organisations that provide social support to clients who identify as sexual minorities. © 2021 Australian Association of Social Workers.
Keywords: LGBTQIA+ people; adult; article; attention; correctional facility; dept.swk; female; gaze; gender identity; human; interview; language; male; masculinity; organization; peer-reviewed; security; social environment; social norm; social support; social work practice; thematic analysis

Healthcare-induced trauma in correctional facilities: a qualitative exploration. - Elumn, Johanna; Keating, Layne; Smoyer, Amy B.; Wang, Emily A. (Health & justice, 2021)
Background: While incarcerated people are known to experience trauma at higher rates than the general population, little is known about how the correctional health system contributes to trauma rates. Methods: We conducted 20 semi-structured qualitative interviews with men who were recently released from a correctional system to understand their experiences with healthcare systems and medical staff during incarceration. Using reflexive thematic analysis within a critical realist framework, we coded and analyzed the data iteratively to refine and unify emerging themes. Results: The unanticipated concept of healthcare-induced trauma emerged and was revealed in three overall themes: (1) healthcare leading to fear of serious illness or death, (2) healthcare leading to fear of people, including healthcare providers, correctional staff, and other incarcerated people, and (3) the correctional institutional, social, and physical environment leads to fear of place. Conclusions: Healthcare in correctional settings has the potential to induce trauma, even when the medical conditions addressed are not life-threatening. Future research should examine the factors contributing to the development of healthcare-induced trauma in correctional settings and develop interventions to prevent and address this phenomenon. © 2021, The Author(s).
Keywords: dept.swk; peer-reviewed